The effect of financial performance on financial distress at PT Garuda Indonesia (Persero) Tbk - Lestari, Putri Indah; Fitranita, Vika (Proceeding International Conference on Accounting and Finance, 2024)
This study aims to determine the effect of PT Garuda Indonesia’s financial performance on the company’s financial distress, focusing on the financial ratios of liquidity, leverage, and profitability. This study uses quantitative methods using secondary data. The sample of this study is the quarterly financial statements of PT Garuda Indonesia from the first quarter of 2015 to the fourth quarter of 2022 using documentation studies as a sampling method. The data was analyzed using multiple linear regression. The results showed that liquidity proxied by current ratio (CR) and profitability proxied by return on assets (ROA) affect the financial distress of PT Garuda Indonesia, while leverage proxied by debt to assets ratio (DAR) has a negative and significant effect on on PT Garuda Indonesia’s financial distress.